KINERJA PEREKONOMIAN KABUPATEN SINTANG - B01110098, Ermi Megawati Megawati (Jurnal Pembangunan dan Pemerataan, 2016)
This research titled â€œEconomic Performance in Sintang Regencyâ€. This research aims to know and analyze economic performance (the pattern change of structure) Sintang Regency from 2008â€“2012. This research used the quantitative method which using analysis Klassen Typology and analysis Shift Share to know the performance of each sectors.Discourse of growth West Borneo Province where Sintang will be planned as the candidate capital of Kapuas Raya Province. Based on the calculation results using analysis of Klassen Typology and Shift Share, from nine sectors in Sintang Regency, actually even though sectors or sub sectors classified as advanced sector and potential sector, donâ€™t show performance that it has always good, also otherwise contrary, that happened in sector or sub sectors classified as backward sectors or progress sector. The only sector classified as advanced sector and has good performance only sector of trade, hotel, and restaurant especially sub sector of wholesale and retail trade. Almost of progress sector, potential, and backward have not good performance even worse. So that, agriculture sector and forestry sector which classified as potential also has bad performance.Taxes that have been imposed in sector or sub sector in Sintang Regency for 2008â€“2012 only consist of 7 Regency or City taxes. The taxes are hotel taxes, restaurant taxes, entertainment taxes, advertisement taxes, street lighting taxes, nonâ€“metallic minerals and other stones, also Tax on Acquisition of Land and Buildings.Keywords: Economic Performance, Shift Share, Klassen Typology, EconomySectors, and Taxes of each sectors.